Analisis Media Pembelajaran Menggunakan Smart TV di SD Negeri 26 Pekanbaru - Ulfah Sarliana Zakiyah; Dea Mustika; Zahratul Hayati; Rila Sahadana; Haikal Hakimi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The use of technology-based learning media, such as Smart TVs, has great potential in improving the quality of learning in elementary schools (SD). Smart TVs can support interactive learning, enrich teaching materials, and increase student learning motivation. However, in reality, many elementary schools still face limited supporting facilities so that their use is not optimal. This study analyzes the use of Smart TV in elementary schools with limited infrastructure, teacher readiness, and its impact on the learning process. The analysis method was carried out qualitatively through the study of school conditions, observations, and interviews with teachers. The results of the study show that the limitations of the internet network, the lack of supporting devices, and the lack of teacher training are the main factors that hinder the effectiveness of the use of Smart TVs. The impact of these limitations is the low integration of technology in learning, limited access to digital materials, and the suboptimal role of teachers as facilitators. Therefore, policy support from the government, improving school facilities, and teacher training programs are needed so that the use of Smart TVs can run optimally. The conclusion of the study emphasizes that Smart TV has the potential to become an innovative learning medium in elementary schools if supported by adequate infrastructure facilities and teacher competence in accordance with the demands of the digital era.